The Arabidopsis thaliana AGRAVITROPIC 1 gene encodes a component of the polar-auxin-transport efflux carrier - Chen, Rujin (The National Academy of Sciences, 1998)
Auxins are plant hormones that mediate many aspects of plant growth and development. In higher plants, auxins are polarly transported from sites of synthesis in the shoot apex to their sites of action in the basal regions of shoots and in roots. Polar auxin transport is an important aspect of auxin functions and is mediated by cellular influx and efflux carriers. Little is known about the molecular identity of its regulatory component, the efflux carrier [Estelle, M. (1996) Current Biol. 6, 1589–1591]. Here we show that mutations in the Arabidopsis thaliana AGRAVITROPIC 1 (AGR1) gene involved in root gravitropism confer increased root-growth sensitivity to auxin and decreased sensitivity to ethylene and an auxin transport inhibitor, and cause retention of exogenously added auxin in root tip cells. We used positional cloning to show that AGR1 encodes a putative transmembrane protein whose amino acid sequence shares homologies with bacterial transporters. When expressed in Saccharomyces cerevisiae, AGR1 promotes an increased efflux of radiolabeled IAA from the cells and confers increased resistance to fluoro-IAA, a toxic IAA-derived compound. AGR1 transcripts were localized to the root distal elongation zone, a region undergoing a curvature response upon gravistimulation. We have identified several AGR1-related genes in Arabidopsis, suggesting a global role of this gene family in the control of auxin-regulated growth and developmental processes.